Pengaruh Latihan Sirkuit terhadap Kemampuan Smash pada Pemain Bola Voli Club ISPRI Kota Palembang - Alvino Verliansyah; Agung Mahendra; Hengki kumbara (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The problem in this research is that the volleyball players at the Ispri Club, Palembang City, have not mastered the smash ability well. The aim of this research was to determine whether there was an effect of circuit training on the smash ability of Club Ispri volleyball players in Palembang City. The research method is an experimental method. The research design is a one group pretest posttest design. The population is 16 athletes. The sample was taken using a total population technique of 16 people. The data collection technique uses a smash ability test. Data analysis uses statistical analysis with the t test. The research results showed that there was a change in the average ability of students in smashing before being given treatment, where the player's ability increased by (19.64) points to (21.77) points after being given four-post circuit training. There is a significant influence of circuit training on the smash ability of the Ispri Palembang City volleyball club because tcount > ttable (9.604 > 1.73) at α 0.05.